Influence stress Work and Income to Satisfaction Work Civil Servants in the General Section Cirebon City Regional Secretariat with Workload as Intervening Variables - Andinna Ananda Yusuff (PT Inovasi Pratama Internasional, 2022)
This study aims to find out how the influence of work stress and income on job satisfaction of civil servants at the General Section of the Regional Secretariat of Cirebon city with Workload as an Intervening Variable. The research results show that, based on the results of the analysis of hypothesis 1, it can be seen that the variable Job Stress (X1) has an effect on the Workload variable (Z). Based on the results of the analysis of hypothesis 2, it is known that the second hypothesis is accepted, meaning that the income variable (X2) affects the workload variable (Z). Based on the results of the analysis of hypothesis 3, it can be seen that it can be concluded that the third hypothesis is rejected, meaning that the Job Stress variable (X1) has no effect on the Job Satisfaction variable (Y). Based on the results of the analysis of hypothesis 4, it can be concluded that the fourth hypothesis is accepted, meaning that the compensation variable (X2) affects the performance variable (Y). Based on the results of the analysis of hypothesis 5, it can be concluded that the fifth hypothesis is rejected, meaning that the Loyalty variable (Z) has no effect on the Performance variable (Y). Based on the results of the intervening test, the indirect effect through the Workload variable (Z) is smaller than the direct effect on the Job Satisfaction variable (Y). Based on the results of the intervening test, the indirect effect through the Workload variable (Z) is greater than the direct effect on the Job Satisfaction variable (Y).